O jovem como sujeito social - Juarez Dayrell (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
This article discusses how young working-class people construct determined ways of being young based on their daily existence. In this construction, they question a series of notions and current representations of youth. The text takes as its focus the daily life of members of rap and funk musical groups seeking to go beyond their participation in musical groups and to reveal their condition as young people. It demonstrates that young people, mediated by fashions, reelaborate the current images of youth, by creating their own ways of being young and demand their right to youth.